The Essence of Siganjua Lalai Values in Dance Movements of Minangkabau Women - Astuti, Fuji (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
Customary and cultural values are an important part which may be found not only in daily routines, but also reflected in all actions, particularly in art. Women’s smooth characteristic in Minangkabau tradition is called siganjua lalai. This research needs to be conducted since some choreographers make princess dance using masculine movements. This research aims at studying and finding the basic concept of women’s dance movements according to the concept of siganjua lalai. This research employs qualitative and experimental methods with social approach of Minangkabau culture. Analyzed using interpretive qualitative techniques, the data are in the form of siganjua lalai dance movement concept, including the design of 1) space, 2) time and 3) energy. The experiment was conducted with students of Sendratasik Study Program, Faculty of Languages and Arts, Padang State University. Based on the research results, the basic patterns of siganjua lalai cover attitudes, leg and arm movements. The philosophy also considers the space, time, and energy. Therefore, the pattern design refers to the philosophy of siganjua lalai. The dance may be expressed in accordance with Minangkabau women’s characteristics in reflecting their cultural identity.